Peran Guru terhadap Aktivitas Bermain Anak Usia Dini - Witri Intan Ardi; Rika Devianti (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2021)
Education is a means for teachers to provide knowledge and experience as well as values ​​in life. For this reason, teachers are to provide a comfortable and joyful learning atmosphere for students, one of which is playing activities. In playing activities, students often behave badly, such as scuffle, and being selfish. This requires a teacher to be able to educate and facilitate them not to do so. This research was to recognize the teachers’ role in early childhood playing activities, especially at As-Salam Kindergarten, Pekan Arba, Tembilahan. This research is descriptive qualitative. The data were collected using structured interview techniques, observation, and documentation. The informants of the research were 3 teachers, a headmaster, head of foundations, and 38 students. The data were analyzed using the data triangulation technique by the Miles and Huberman model. The results showed that the teachers play a vital role as designers, observers, models, facilitators, elaborators, and evaluators.